Beach and Trough Stability Study of the Xiyang Sea Area of Jiangsu Province. Issue 2 (September 2019) - Jun, Chen; Fan, Zhu
Abstract: The dynamic geomorphology of the Xiyang sea area, the largest tidal channel in the northern part of the Radial Sand Ridges in the South Yellow Sea, is complex. This paper studies the tidal flat and tidal channel stability and the evolution of the coast off the Xiyang sea area by combining topographic surveys in different periods with the data from remote sensing satellites. The result shows that the state of west tidal flat of the Xiyang tidal channel has changed from long-term siltation to dynamic balance of erosion and siltation. The Dongsha Sand Ridges on the eastern side of the Xiyang tidal channel has moved eastward and southward. The exchange of water and sand in the seas of Piaoersha and Sanyazi sand ridges was frequent with no significant rules of erosion and siltation.